Early genomic detection of cosmopolitan genotype of dengue virus serotype 2, Angola, 2018 - Hill, S; Neto De Vasconcelos, J; Gutierrez Granja, B; Theze, J; Jandondo, D; Neto, Z; Mirandela, M; Santos Sebastiao, C; Micolo Candido, A; Clemente, C; Pereira Da Silva, S; Oliveira, T; et al. (Centers for Disease Control and Prevention, 2019)
We used portable genome sequencing to investigate reported dengue virus transmission in Angola. Our results show that autochthonous transmission of dengue serotype 2 (cosmopolitan genotype) occurred in January 2018.